Pemberian Minum Air Hangat dalam Meningkatkan Bersihan Jalan Nafas pada Pasien Asma di Instalasi Gawat Darurat - Lia Safina; Dheni Koerniawan; Sanny Frisca (Pusat Riset dan Inovasi Nasional, 2026)
Asthma is a heterogeneous disease characterized by chronic inflammation of the airways and respiratory symptoms such as wheezing, shortness of breath, chest tightness, and cough, which vary over time in both frequency and severity. This condition is accompanied by limitations in expiratory airflow, which can be either reversible or persistent. In asthma patients, especially those treated in the Emergency Department (ED), a common nursing problem is ineffective airway clearance due to mucus accumulation and bronchospasm. One strategy to address this is the administration of warm drinking water, aimed at improving airway clearance. The design used in this final nursing scientific paper is a qualitative case study with an intervention of warm water intake. The subjects of this study consisted of 3 asthma patients in the ED, and the intervention was conducted from January 3-11, 2026, at the Emergency Department of Charitas Hospital Km.7 Palembang. Airway clearance was measured before and after the intervention, which involved giving 200 ml of warm water at 38ºC, without a control group. After the intervention, all three patients showed improved airway clearance, indicated by more effective coughing, decreased sputum production, reduced wheezing, improved breathing patterns, and improved respiratory rate. The implementation of this evidence-based practice (EBP) is expected to provide additional information regarding the use of nonpharmacological therapy, specifically the administration of warm drinking water, in asthma patients with ineffective airway clearance.